Analysis of Students' Mathematical Literacy Skills in Solving Pythagorean Theorem Problems Based on Gender Differences - Rohil Rohil; Putri Wahyuni; Indah Widiati; Suripah Suripah (The Future of Education Journal, 2026)
This study aims to describe students' mathematical literacy skills in solving problems related to the Pythagorean Theorem from a gender perspective. The mathematical literacy indicators employed in this study include: (1) identifying mathematical statements and questions; (2) representing the identified information by interpreting and using tables, diagrams, or figures; (3) constructing mathematical models based on the given problems; (4) applying the mathematical models to solve the problems; and (5) drawing conclusions supported by appropriate reasoning. This study adopted a qualitative approach involving 35 students, comprising 18 male students and 17 female students. Data were collected through an essay-based mathematical literacy test and semi-structured interviews. The findings indicate that female students demonstrated higher mathematical literacy skills than male students across all assessed indicators of mathematical literacy.